Temporal dynamics of land use, physical attributes, and hemeroby in the municipality of Sorocaba (SP): Insights for planning in metropolitan municipalities - Silva, Fabio Leandro da; Smith, Welber Senteio; Cunha-Santino, Marcela Bianchessi da; Bianchini Júnior, Irineu; Menezes, Denise Balestrero (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Monitoring land use and land cover patterns, evaluating physical environmental attributes, and utilizing landscape indicators, such as hemeroby can significantly aid in the planning and preservation of ecosystem services. This study aimed to analyze the temporal dynamics of land use/land cover in the city of Sorocaba (SP) between 2007 and 2017, as well as the characteristics of the physical environment (i.e., slope and hypsometry) and hemeroby, aiming to provide elements for planning. The results showed the predominance of typologies: urbanized area; native vegetation; pasture; and temporary crops. The municipality’s area is characterized by a low variation in hypsometric classes and a low slope, which favors territorial occupancy. The predominant levels of hemeroby are euhemerobiotic and metahemerobiotic, both reflecting significant anthropogenic interference, low self-regulation capacity, and an overriding need for human management and technological dependence. Therefore, urban expansion projects should consider the characteristics of the territory and adopt measures that minimize environmental impacts, facilitating the transition of landscape units with high hemeroby to levels with less anthropogenic interference and technological dependence.